Rejeição da ajuda humanitária como violação aos direitos humanos? uma análise jurídico-política do bloqueio da ajuda humanitária ofertada à Venezuela em fevereiro de 2019 - Andrade, Polyanna Figueirêdo de (2021)
This dissertation analyzes the legality and legitimacy of the rejection of humanitarian aid offered to the Venezuelan government in February 2019 in the city of Cúcuta, Colombia. The occurrence gained international repercussions by counterposing humanitarian and human rights issues to the guarantee of state sovereignty, marked by the frustrated attempt to send humanitarian assistance from the United States and Brazil to Venezuelan territory at the request of Juan Guaidó, opposition leader. Thus, the hypothesis to be verified is the legality and legitimacy of the blockade of humanitarian aid ordered by President Nicolás Maduro, since the donor countries acted driven by political interests, which would mischaracterize the humanitarian assistance offered. Aiming to enable said investigation, it was initially necessary to thoroughly study the fact that gave rise to this research, namely the blockade of the Las Tienditas cross-border bridge in Cúcuta, Colombia, a city that borders Ureña, belonging to Venezuela, in February 2019. After presenting the situation that is the target of doubt, in order to seek legal grounds for the solution of the problem, the concepts and foundations of International Human Rights Law and International Humanitarian Law are studied, guiding the international relations of Public International Law. It is noted that both are still ineffective in expressly regulating the humanitarian treatment of domestic conflicts, leaving only analogy as an instrument of legality. In turn, moving on to the political sphere, the study sought to find the political foundations for what happened, verifying that the current relations between Venezuela, Brazil, and the United States stem from a series of events involving disputes of interests. In the end, the hypothesis raised initially was proven to be true, i.e., the legality and legitimacy of the Venezuelan border blockades preventing the entry of humanitarian aid sent by the United States and Brazil, since it was proven that the Americans had in fact introduced political issues to be accomplished with the successful delivery of the assistance, a politicization that mischaracterizes it and jeopardizes the whole legitimacy of the humanitarian relief structure. As for the methodology adopted, it follows the dialectic method, making a dynamic analysis of reality to understand the Venezuelan crisis through the dialogue between the social, political and economic contexts in that country, complemented with the qualitative approach and the bibliographic-documentary procedure. Furthermore, as to the objectives, it will be descriptive and explanatory, since data was collected to verify the causes of the existing phenomenon. At the end of this research it was concluded that the politicization of humanitarian aid practiced by the United States guaranteed Venezuela the recognition of the legality and legitimacy of the rejection of aid through the closing of borders, not being this act a violation of human rights. However, it was also found that the way President Nicolás Maduro reprimanded the opposition civilians was a demonstration of excessive use of force and, as such, a violation of essential human rights.